Evaluation of single-frequency receivers for studying crustal deformation at the longitudinal Valley fault, eastern Taiwan. Issue 374 (2nd September 2020) - Chen, Horng-Yue; Tung, Hsin; Hsu, Ya-Ju; Lee, HungKyu
Abstract : Applications of low-cost single-frequency continuous GPS receivers for monitoring volcano and landslide activities as well as to complement dual-frequency receivers have been demonstrated to produce stable and accurate positioning. In studies of crustal deformation, the relative distance between monitoring stations may vary from several kilometers to tens of kilometers, hence the differential single-frequency observations cannot model the ionospheric delay or other distance dependent errors. The 55 low-cost single-frequency continuous stations have been deployed together with 52 continuous dual-frequency stations in southeastern Taiwan since 2008. All of the single-frequency stations have applied corrections using dual-frequency stations to eliminate the distance dependent errors. Comparing velocity estimates from 8 co-located, the differences in horizontal and vertical components are less than 3 mm/yr and 6 mm/yr, respectively. Our study shows that the combination of single- and dual-frequency GPS data can provide robust results to study the fault slip behavior on the Longitudinal Valley fault.